Spreading of hepatitis C virus subtypes 1a and 1b through the central region of Argentina - Culasso, Andrés Carlos Alberto (2014)
The recent history of the hepatitis C virus (HCV) subtypes 1a and 1b in the central region of Argentina is hypothesized by phylogeographic reconstruction using coalescent based Bayesian analyses. Direct partial E2 sequences from HCV 1a and 1b infected patients attending different health-care centers of the country were analyzed. The inferred date of the most recent common ancestor (tMRCA) for HCV-1a was: 1962 (between 1943 and 1977) and for HCV-1b was earlier: 1929 (between 1895 and 1953). Diverse ancestral populations were inferred from both subtypes in Córdoba and in Buenos Aires cities and after that, HCV spread within and between larger cities and to other smaller cities. The analyses suggested that HCV-1b was dispersed first and it is currently in a stationary phase whereas HCV-1a was dispersed latter and it is still in a growth phase. Finally, as it was observed in the developed countries, while the transmission of HCV-1b appears to have been somehow prevented, the HCV-1a may still represent a concern in the public health. Further work should be carried out to address their current transmission rate (and its main transmission route) in the Argentinean population.